2019
DOI: 10.1016/j.neurobiolaging.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Using stem cell–derived neurons in drug screening for neurological diseases

Abstract: Induced pluripotent stem cells (iPSCs) and their derivatives have become an important tool for researching disease mechanisms. It is hoped that they could be used to discover new therapies by providing the most reliable and relevant human in vitro disease models for drug discovery. This review will summarise recent efforts to use stem cell-derived neurons for drug screening. We also explain the current hurdles to using these cells for high throughput pharmaceutical screening and developments that may help over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 146 publications
0
39
0
Order By: Relevance
“…Stem cell-based models can also be used to screen drugs for treatment of neurodevelopmental disorders including ASD [91,104]. For example, one study screened 4421 unique compounds and identified 108 compounds that regulate neurite growth [105], a process which has been variably linked to some forms of ASD [106].…”
Section: Drug Discoverymentioning
confidence: 99%
“…Stem cell-based models can also be used to screen drugs for treatment of neurodevelopmental disorders including ASD [91,104]. For example, one study screened 4421 unique compounds and identified 108 compounds that regulate neurite growth [105], a process which has been variably linked to some forms of ASD [106].…”
Section: Drug Discoverymentioning
confidence: 99%
“…To investigate whether this is the case, human induced pluripotent stem cell (hiPSC)-derived neurons can be used. It is known that there is variability between different hiPSC-derived neuronal cell lines 54 . This could be the result of the generation protocol or the maturation stage in which the neurons were frozen.…”
Section: Effects Of Pfas On Rat Cortical Network Activitymentioning
confidence: 99%
“…Stem cell technology, in particular human stem cells, has been transforming the fields of toxicology and pharmacology by providing noncancerous human‐specific cell models for research applications and detection of biologic activity of toxins and pharmaceuticals . While early studies were limited by controversies surrounding the use of embryonic stem cells, discoveries leading to the ability to efficiently re‐program adult human cells into human‐induced pluripotent stem cells (hiPSCs) have led to an explosion in progress in this field.…”
mentioning
confidence: 99%